MEAN CENTERING OF RATIO SPECTRA METHOD FOR THE ANALYSIS OF THEOPHYLLINE AND EPHEDRINE HCL MIXTURE IN TABLET - Muchlisyam; Sudarmi; Caroline, Cindy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Mean centering of ratio spectra method (MCR method) is one of the simplest methods for the determination of drug mixtures. The purpose of this research is to determine the content of theophylline (THEO) and ephedrine HCl (EPH) in tablets by MCR spectra method. Methods: This research was conducted with the MCR method. It was measured at 271 nm for THEO and 257 nm for EPH using 0.1 N HCL as a solution. The calculation was conducted with Matlab application. The analytical characteristics of the method are detection limit, accuracy, precision, and selectivity. Standard addition method was used to increase the concentration of EPH in the sample until it reached the range of calibration concentration. Result: The research has showed that validations for THEO were 100.57% for accuracy, 0.68% for relative standard deviation (RSD), 0.46 Î¼g/mL for limit of detection (LOD), and 1.52 Î¼g/mL for limit of quantification (LOQ). Meanwhile, the validations for EPH are 100.02% for accuracy, 0.07% for RSD, 43.12 Î¼g/mL for LOD, and 143.72 Î¼g/mL for LOQ. The level of THEO is 97.43 Â± 0.17% and the level of EPH is 101.36 Â± 0.25% for brand one’s tablet. Meanwhile, brand two’s tablet contains 98.72 Â± 0.14% of THEO and 103.62 Â± 0.23% of EPH. Conclusion: MCR ultraviolet spectrophotometric method can be used to determine the content of THEO and EPH in tablets and meets the detection limit, accuracy, precision, and selectivity.